Pain management in hospitals: patients' satisfaction and related barriers - Tawil S; Iskandar K; Salameh P (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Background: Suboptimal pain control has been frequently reported in healthcare settings and documented to negatively impact patients' health. Patients' perception regarding pain management may influence their satisfaction regarding treatment. Objectives: This study focuses on the assessment of patients' satisfaction regarding pain therapy and defining patient-related barriers for its implication. Methods: A cross-sectional study was conducted in two tertiary care hospitals from April till July 2017. A face-to face interview questionnaire was filled regarding pain scores and patients' attitudes regarding pain management. Both medical and post-surgical adult patients with all types of pain were eligible to participate. A descriptive analysis of patient satisfaction and perceptions regarding pain management was done. Results: Results from 183 participants with a mean age of 49 (SD=17.33) revealed that pain was their main reason for hospitalization (71.6% of the cases). Numeric pain scores were recorded only in 14.2% of the patient medical files. Pain intensity documentation by healthcare professionals was found in 41.5% of the cases, and 7.7% of the patients had to wait for more than 30 minutes before getting the pain medication. Around 85% of the patients were satisfied with their pain management. Patients' barriers to effective pain therapy were mainly fear of adverse effects, addiction, and additional costs (p<0.05). Conclusions: Pain remains a prevalent problem that requires more efforts for improvement. Our study can effectively serve as a start for larger studies where barriers to pain management can be assessed as an independent variable affecting pain management practice.